2017
DOI: 10.22158/sll.v1n2p86
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Using Asking for Clarification and Circumlocution Speaking Strategies on Enhancing the Speaking Skill of EFL Students

Abstract: This study mainly aimed at investigating the impact of teaching the asking for clarification

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…The results of this study, which is the first study on the effects of the training for explanation with different words strategy in Turkish literature, seem to be compatible with the results of many studies (Baradeyah & Farrah, 2017;Campillo, 2006;Scullen & Jourdan, 2000;Salomone & Marsal, 1997) conducted within the framework of foreign language teaching in international literature. In these studies, it has been reported that the training for explanation with different words strategy has significant contributions especially to the speaking skill.…”
Section: Findings Discussion and Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The results of this study, which is the first study on the effects of the training for explanation with different words strategy in Turkish literature, seem to be compatible with the results of many studies (Baradeyah & Farrah, 2017;Campillo, 2006;Scullen & Jourdan, 2000;Salomone & Marsal, 1997) conducted within the framework of foreign language teaching in international literature. In these studies, it has been reported that the training for explanation with different words strategy has significant contributions especially to the speaking skill.…”
Section: Findings Discussion and Resultssupporting
confidence: 90%
“…Türk alan yazınında farklı kelimelerle açıklama stratejisi eğitiminin etkileri üzerine yapılan ilk çalışma olma özelliği taşıyan bu araştırmada elde edilen sonuçlar, uluslararası alan yazında yabancı dil öğretimi çerçevesinde gerçekleştirilen birçok araştırmanın sonucu ile (Baradeyah & Farrah, 2017;Campillo, 2006;Scullen & Jourdan, 2000;Salomone & Marsal, 1997) uyumlu görünmektedir. Bu araştırmalarda da farklı kelimelerle açıklama stratejisi eğitiminin, özellikle konuşma becerisine önemli katkılarının olduğu rapor edilmiştir.…”
Section: Tartışma Ve Sonuçunclassified
“…Therefore, much research has focused on developing EFL learners' speaking skill by implementing various approaches (e.g. Alzboun et al, 2017;Baradeyah & Farrah, 2017;Delliou & Zafiri, 2016;Derakhshan et al, 2016;Manurung, 2015;Saeed et al, 2016).…”
Section: ‫أﺳﻠﻮب‬ ‫اﺳﺘﺨﺪام‬ ‫أﺛﺮ‬ ‫اﻟﺼﻒ‬ ‫ﻃﻠﺒﺔ‬ ‫أداء‬ ‫ﻋﻠﻰ‬ ‫اﻟﺤﻮاري‬ ‫اﻟﺘﺪرﻳﺲ‬ ‫اﻟﺘﺤﺪث‬ ‫ﻣﻬﺎرة‬ ‫ﻓﻲ‬ ‫اﻟﺴﺎﺑﻊ‬mentioning
confidence: 99%